Hubungan Pola Makan Dengan Kejadian Anemia Pada Remaja Di SMP Negeri 9 Kota Bima - Lestari, Humaediah; Afrianti, Dian; Hardiani, Sri (Bunda Edu-Midwifery Journal (BEMJ), 2022)
Anemia is a condition in which the level of hemoglobin in the blood is less than normal. Adolescents are at risk of developing anemia and are susceptible to malnutrition because of rapid growth and development and sufficient energy is required to perform various physical activities. If the intake pattern of nutrition is poor, it will have an impact on growth and development that is not optimal, and is more susceptible to chronic diseases in adulthood. Data obtained from the Bima City Health Office regarding cases of anemia in adolescent girls over the last three years has continued to increase. Based on these problems, this study aims to determine the relationship between dietary habit and the incidence of anemia in adolescent girls at SMP Negeri 9 Bima City in 2021. The research design used an analytical survey design with a cross sectional approach. The population in this study were all female students who were in SMP Negeri 9 Bima City. Sampling in this study used a total sampling technique with a total of 87 students. The instrument in this study used a questionnaire and Hb Check using the HB Stick. Data analysis used the chi square test with a significant level of 0.05. The results showed that the majority of adolescent girls in SMP Negeri 9 Bima City had a good dietary, namely 54.0%, while those with anemia were 42.5%. The results of the chi square test analysis obtained a significance value = 0.517 exceeding the significance level = 0.05, thus there is no relationship between dietary habit and the incidence of anemia. Based on the results of the study, it was shown that the majority of the female students in SMP Negeri 9 Bima City had a good dietary and experienced anemia, so it was suggested to the school to encourage to collaborate with the Health Center to provide counseling about anemia, blood boost tablets(Fe) and adolescent lifestyle in healthy way.